Dimensi Sosial dalam Wacana Tafsir Audiovisual: Studi atas Tafsir Ilmi, “Lebah Menurut al-Qur’an dan Sains,” Lajnah Pentashihan Mushaf al-Qur’an Kemenag RI di Youtube - Hamdan, ALi; Miski, Miski (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2019)
This article departs from the reality of the presence of an audiovisual interpretation, "Lebah menurut al- Qur‟an dan Sains" by the Lembaga Pentashihan Mushaf al-Qur‟an (Pentashihan Mushaf al-Qur'an Institute) of the Ministry of Religion in Indonesia have never been reviewed. In fact, with this interpretation, Pentashihan Mushaf al-Qur'an Institute has produced and translated scientific interpretations of waf which are actually still polemic in the midst of observers of the study of the Quran. So, the question to be answered in this study is: "What is the social dimension in the audiovisual interpretation “Lebah menurut al-Qur‟an dan Sains?" This article is qualitative study with a type of literature study; a complete video containing documentation with primary material "Lebah menurut al-Qur‟an dan Sains” and supported with other written materials. This article shows two main things about the scientific interpretation of the discourse through video 'Lebah menurut al-Qur‟an dan Sains, "by Pentashihan Mushaf al-Qur'an Institute so that it was not immediately accepted, firstly, by its role as an institution that has relations and the legitimacy of forces under the protection of state institutions. Second, the position held by Pentashihan Mushaf al-Qur'an Institute is strengthened with the reality others they have asked for more to facilitate discourse for audiences; access with the support of important figures in and fully supported by access to support the sophistication of technology and information.